2013
DOI: 10.1159/000350611
|View full text |Cite
|
Sign up to set email alerts
|

Post-Dilution High Convective Transport Improves Microinflammation and Endothelial Dysfunction Independently of the Technique

Abstract: Background/Aims: We examined the effects of different online hemodiafiltration techniques on microinflammation and endothelial damage/repair. Methods: The study was designed as a prospective crossover study. Flow cytometry was used to measure CD14+CD16+ monocytes, apoptotic endothelial microparticles (EMPs), and endothelial progenitor cells (EPCs). Results: Patients treated with high-flux hemodialysis showed a marked chronic inflammatory state (HF-HD 11 ± 2) versus healthy subjects (HS 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
(52 reference statements)
2
21
0
1
Order By: Relevance
“…On contrary, CD14+ CD16+ monocytes subsets that are observed in high proportion in CKD patients may be involved in vascular impairment [34] . An inverse correlation between CD14+ CD16+ level and EPCs number has been observed [35][36][37] . Our results are in line with these observations, suggesting that both circulating pro-inflammatory monocytes and activated T cells are associated with a poor mobilization of EPCs.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…On contrary, CD14+ CD16+ monocytes subsets that are observed in high proportion in CKD patients may be involved in vascular impairment [34] . An inverse correlation between CD14+ CD16+ level and EPCs number has been observed [35][36][37] . Our results are in line with these observations, suggesting that both circulating pro-inflammatory monocytes and activated T cells are associated with a poor mobilization of EPCs.…”
Section: Discussionmentioning
confidence: 88%
“…Using this study design each patient acted as his own control, which improves reproducibility and facilitates explorations of biological modifications associated with dialysis modalities. Previous studies have observed the reduction of the percentage of proinflammatory CD14+ CD16+ monocytes using high-flux one line hemofiltration [34,35,37] . This reduction of microinflammation may improve EPCs mobilization and endothelial damage/repair imbalance.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Este proceso inflamatorio mejora con la utilización de técnicas alternativas a la HD convencional como es la hemodiafiltración en línea (HDF-OL), que consigue mejorar los aclaramientos de toxinas urémicas al aumentar esta técnica el transporte convectivo [4][5][6] . Para la realización de esta técnica, es necesario la utilización de una membrana de alto flujo, capaz de mantener durante la sesión una ultrafiltración elevada en ausencia de complicaciones técnicas en el circuito extracorpóreo, al mismo tiempo que se requiere el suministro de líquido de reposición para compensar el exceso A comparative analysis between online hemodiafiltration and hemodiafiltration with endogenous reinfusion: clinical, technical and inflammatory parameters.…”
Section: Introductionunclassified